Thrips on eggplant, chilli and bell pepper in Cameron Highlands, Malaysia - Tan, Jiunn Luh; Ooi, Peter Aun Chuan; Khoo, Gideon (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Thrips have always been one of the major pests for eggplant (Solanum melongena L.), chili and bell peppers (Capsicum annuum L.). Thrips damage these vegetable crops either by direct feeding on the leaves, flowers or fruits or they act as vectors for viruses. However, not all thrips feed on the above-mentioned crops, thus identification of the thrips that feed on these vegetable crops is important in order to provide an effective solution. Therefore, the objective of this study is to identify the species of thrips that attack these plants and cause major damages. Cameron Highlands was microscopic glass slides using Euparal as mounting medium. The thrips specimens were identified based on the morphology. The thrips that were found abundant on these vegetable crops were Thrips palmi Karny and Thrips parvispinus Karny. These thrips were usually found feeding in the flowers of susceptible vegetable crops. There were on average 5 thrips per flower. The damage of thrips can only be observed during fruit formation as scars on the external surface of the fruits. The damage became intensified as the fruits grew to cause them to develop irregular shapes and dry-looking. These unpleasant looking fruits, although edible, are not preferred by consumers, thus causing them to be non-marketable.selected as the study area because it is one of the major vegetable production areas in Malaysia. Thrips were collected from several farms in Cameron Highlands. The thrips samples were stored in 70% ethanol, macerated by soaking in weak sodium hydroxide (5% NaOH), dehydrated using alcohol and clove oil and finally mounted on